ELECTRON BEAM DEPOSITION OF BORON-BASED COATINGS UNDER VACUUM PRESSURE AND EXPERIMENTAL RESULTS OF NITROGENATION IN ELECTRON BEAM PLASMA - Abdullayev, Lazizbek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
When using optimal modes, energy consumption is (170-190) W / cm2. It matches most of the properties of electrolytes for anodic heating. It was found that the following structures are formed in boron coating: oxide zone (Fe3O4, Fe2O3, FeO) and nitride-martensite layer (Fe3N, martensite and retained austenite). The method of backscattering protons from the nucleus made the concentration of boron in the layer 13% and nitrogen - 11%. After anodizing the needles, their microhardness increases from HB=54-60 to HB=135-150, that is, the microhardness of their work surface increases 2.5-3 times. The increase in the microhardness of the needles leads to a decrease in the cost of replacing them with a new one, as a result of which they are slightly (2-3 times) less bent and broken during the sewing process. After anodic boron-nitriding of the needles, their working surfaces increase the service life of the needles by at least 3 times.